Close correlation between thiolate basicity and certain NMR parameters in cysteine and cystine microspecies - Ferreira de Santana, Juliana; Mirzahosseini, Arash; Mándity, Beáta; Bogdán, Dóra; Mándity, István; Noszál, Béla (PLOS ONE, 2022)
The imbalance between prooxidants and antioxidants in biological systems, known as oxidative stress, can lead to a disruption of redox signaling by the reactive oxygen/nitrogen species and is related to severe diseases. The most vulnerable moiety targeted by oxidant species in the redox signaling pathways is the thiol (SH) group in the cysteine residues, especially in its deprotonated (S−) form. Cysteine, along with its oxidized, disulfide-containing form, cystine, constitute one of the most abundant low molecular weight biological redox couples, providing a significant contribution to the redox homeostasis in living systems. In this work, NMR spectra from cysteine, cystine, and cysteine-containing small peptides were thoroughly studied at the submolecular level, and through the chemical shift data set of their certain atoms it is possible to estimate either thiolate basicity or the also related standard redox potential. Regression analysis demonstrated a strong linear relationship for chemical shift vs thiolate logK of the cysteine microspecies data. The αCH 13C chemical shift is the most promising estimator of the acid-base and redox character.